“SUBSTITUSI TEPUNG Cucurbita moschata (Duch.) Poir TERHADAP KADAR β-KAROTEN DAN DAYA TERIMA CAKE LABU KUNING” - Frederika Pellu Dimu; Andriani Rafael; Sonya T.M Nge (Indigenous Biologi : Jurnal Pendidikan dan Sains Biologi, 2021)
ABSTRACTPumpkin (Cucurbita moschata (Duch.) Poir ) is one of the vegetables that is rich in β-carotene as a precursor of vitamin A and has a fairly high carbohydrate content. Pumpkin processing can be done to produce various kinds of products, one of which is cake. Cake is a baked dough and liquid dough made from flour, sugar, salt, ingredients, shortening, milk, eggs, and aroma enhancer. This study aims to determine the levels of β-carotene contained in pumpkin cake and to determine the acceptability of β-carotene in pumpkin cake. This research is an experimental research. The experimental design used was Completely Randomized Design (CRD) with 1 control 4 treatments and each treatment was repeated 3 times. The research phase consisted of making flour and making cake. Data collection methods include organoleptic tests and β-carotene tests. Data were analyzed using analysis of variance / ANOVA to determine differences in quality, and if there is an influence then proceed with the Tukey test. Organoleptic test results show that the best treatment of pumpkin cake in terms of color is A1 with a value of 3.88, in terms of aroma namely A0 with a value of 3.92, in terms of texture is A0 with a value of 4.28 and in terms of taste is A0 with value of 4.16. As for the β-carotene test, the treatment of pumpkin cake with the highest β-carotene content was found in A4 with an average of 0.262 and the lowest level was in A0 with an average of 0.018. Based on research data, pumpkin flour is worthy of being used as an alternative source of flour because the resulting cake meets SNI quality standards both in terms of color, taste, aroma, texture and β-carotene content.Keywords : Cake, Pumpkin, β-Carotene, Organoleptic